School Principals’ Leadership Strategies in Creating a Quality Culture: A Systematic Literature Review in Secondary Education - Basuki, Rahmat Rizky; Rahmawati, Desi; Santoso, Heru; Huda, Syafaat Ariful (FKIP - Universitas Riau, 2026)
This study presents a bibliometric review of research on school leadership and educational quality in secondary education published between 2020 and 2025. The study aims to map the conceptual relationships among school leadership, teacher performance, and educational quality, as well as to identify emerging research trends in leadership innovation and quality management. Using a systematic literature review guided by the PRISMA protocol, publications were retrieved from Scopus and Google Scholar and analyzed using bibliometric mapping techniques. The results indicate that school leadership functions as a central connecting variable linking teacher performance and educational quality. Two dominant research trajectories were identified: a traditional focus on teacher professionalism and learning outcomes, and a more recent emphasis on leadership innovation, school-based management, and institutional quality strategies. Overall, the findings highlight the strategic role of school principals in fostering a quality-oriented school culture and suggest the need for future research employing longitudinal and mixed-method approaches to deepen understanding of leadership and quality improvement in secondary education.